50 Years of Pediatric Hemostasis: Knowledge, Diagnosis, and Treatment - Levy-Mendelovich, Sarina; Cohen, Omri; Klang, Eyal; Kenet, Gili (Seminars in Thrombosis and Hemostasis, 2022)
Studies from the past 50 years have contributed to the expanding knowledge regarding developmental hemostasis. This is a dynamic process that begins in the fetal phase and is characterized by physiological variations in platelet counts and function, and concentrations of most coagulation factors and the native coagulation inhibitors in early life, as compared with adulthood. The developmental hemostasis studies since the 1980 to 1990s established the laboratory reference values for coagulation factors. It was only a decade or two later, that thromboelastography (TEG) or (rotational thromboelastometry [ROTEM]) as well as thrombin generation studies, provided special pediatric reference values along with the ability to evaluate clot formation and lysis. In addition, global whole blood-based clotting assays provided point of care guidance for proper transfusion support to children hospitalized in intensive care units or undergoing surgery. Although uncommon, thrombosis in children and neonates is gaining increasing recognition, typically as a secondary complication in sick children. Bleeding in children, and particularly intracerebral hemorrhage in newborns, still represent a therapeutic challenge. Notably, our review will outline the advancements in understanding developmental hemostasis and its manifestations, with respect to the pathophysiology of thrombosis and bleeding complications in young children. The changes of transfusion policy and approach to thrombophilia testing during the last decade will be mentioned. Subsequently, a brief summary of the data on anticoagulant treatments in pediatric patients will be presented. Finally, we will point out the 10 most cited articles in the field of pediatric and neonatal hemostasis.
Keywords: developmental hemostasis; neonates; intracranial hemorrhage; thrombosis; anticoagulants; DOAC